Portrait of the Moronene Women in Folklore Kada: Structural and Semiotic Analysis - Yusniati Rambe (Universitas Sembilanbelas November Kolaka, 2017)
The literary work is closely related to the background of the society that created it. One form of literary work is folklore. Moronene folklore certainly reflect the social and cultural aspects of Moronene society. The female character, also a part of the social and cultural aspects of society. Moronene's female character, according to the Moronene tradition, is possible to be understood through Moronene folklore. This study aims to gain an in-depth understanding of the character of Moronene women in Moronene folklore. This research uses qualitative approach with content analysis method. This research uses a structural and semiotic approach with the female characters in Moronene folklore. This research data is derived from Kada folklore taken using purposive sampling. The data collection instrument is the researcher himself as a key instrument. Data were analyzed using Mayring's (2000) model with structural and semiotic approach. The examination of legalization of data is done by triangulation technique. The research findings show that female characters, based on the Kada folklore structure, reflect women who are consequent to their image and role.